2018
DOI: 10.1002/slct.201802136
|View full text |Cite
|
Sign up to set email alerts
|

Application of Z–Scheme CdSWO3 Nanocomposite for Photodegradation of Ethylparaben under Irradiation with Visible Light: A Combined Experimental and Theoretical Study

Abstract: The CdS- WO3 nanocomposite was successfully synthesized using the hydrothermal method. The catalytic capacity of CdS- WO3 nanocomposite was evaluated based on various parameters, such as pH, catalyst load, bicarbonate and persulfate concentrations. The ratios of CdS to WO3 was also examined to acquire the photocatalytic performance in addition, the by–products and pathway were also studied. The findings showed that CdS- WO3 (ratio 3:7) produced better photodegradation performance in comparison to CdS- WO3 (rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Recently, the coupling of semiconductor with different band gaps revealed that it can suppress the charge carrier recombination rate. Several researchers have reported the application of WO 3 nanocomposite with other semiconductors in the photodegradation of organic pollutants [30][31][32][33], gas sensing [34], pharmaceutical [35,36], and photoelectrochemical applications [37,38]. Tricobalt tetroxide (Co 3 O 4 ) is a p-type semiconductor that possesses unique characteristics of high stability (thermal and chemical), low solubility, catalytic properties [39] as well as having a narrow band gap (2.1 eV) and various oxidation states [40].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the coupling of semiconductor with different band gaps revealed that it can suppress the charge carrier recombination rate. Several researchers have reported the application of WO 3 nanocomposite with other semiconductors in the photodegradation of organic pollutants [30][31][32][33], gas sensing [34], pharmaceutical [35,36], and photoelectrochemical applications [37,38]. Tricobalt tetroxide (Co 3 O 4 ) is a p-type semiconductor that possesses unique characteristics of high stability (thermal and chemical), low solubility, catalytic properties [39] as well as having a narrow band gap (2.1 eV) and various oxidation states [40].…”
Section: Introductionmentioning
confidence: 99%